2008
DOI: 10.1001/archgenpsychiatry.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Polymorphism Near CREB1 With Differential Aversion Processing in the Insula of Healthy Participants

Abstract: Context Previous functional neuroimaging studies have identified a network of brain regions that process aversive stimuli, including anger. A polymorphism near the cyclic adenosine monophosphate response element binding protein gene (CREB1) has recently been associated with greater self-reported effort at anger control as well as risk for antidepressant treatment–emergent suicidality in men with major depressive disorder, but its functional effects have not been studied. Objective To determine whether this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…A study by Juhasz and colleagues showed that CREB can amplify the effect of childhood adversity and increase the risk of MDD [59]. Perlis and colleagues showed that CREB is associated with responsiveness to angry faces in a brain network implicated in processing aversion [60]. These networks develop through interactions with the environment; the neuronal structure and neurotransmission in these networks are constantly being refined through activity-dependent synaptic plasticity in order to optimally process and store relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Juhasz and colleagues showed that CREB can amplify the effect of childhood adversity and increase the risk of MDD [59]. Perlis and colleagues showed that CREB is associated with responsiveness to angry faces in a brain network implicated in processing aversion [60]. These networks develop through interactions with the environment; the neuronal structure and neurotransmission in these networks are constantly being refined through activity-dependent synaptic plasticity in order to optimally process and store relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…MJ scored greater on peer conformity on the MISS than CON (t (1,40) = 2.08, p = 0.044; Fig 2A), and showed a trend toward higher ratings on overall suggestibility, (t (1,40) = 1.96, p = 0.057), though it should be noted that these differences were not significant when corrected for multiple comparisons, ans should be followed up with larger samples for confirmation. Across groups, peer conformity scores were positively associated with vACC activation ( r 2 = 0.10, p = 0.042; Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…We did not extract data from the OFC because neither group showed significant activation in this region. Individual parameter estimates were extracted using the FSL program featquery (http://fsl.fmrib.ox.ac.uk/fsl/fsl4.0/feat5/featquery.html) from anatomical ROIs using masks parcellated from the ICBM152 T1 brain at the MGH Center for Morphometric Analysis (CMA) (39, 40). Values were regressed against peer influence scores, in order to investigate whether brain activation was associated with trait levels of peer conformity.…”
Section: Methodsmentioning
confidence: 99%
“…Activation signal was extracted from using the following steps: (1) the signal at each voxel was converted to a (percentage) deviation from the mean for that voxel across the entire time series, (2) the signal was averaged by stimulus type and spatially translated into MNI space, and (3) anatomical masks were designated consisting of the volume of interest through which each individual participant's data was extracted. All masks were parcellated from the ICBM152 T1 brain at the MGH Center for Morphometric Analysis (CMA) (Gasic et al, 2009; Perlis et al, 2008), using validated anatomical landmarks for the NAc and caudate.…”
Section: Methodsmentioning
confidence: 99%